Desarrollo de una aplicación web y móvil de comercio electrónico para la empresa SOPTEC PC. - Rodríguez Benavides, Karla Evelyng (2021)
This technological proposal was carried out in the company SopTec pc, located in the province of Cayambe Cayambe canton, company in which the problem of an inadequate sales management process was identified, where online sales were made through publications in social networks, this leads to a continuous waste of time, for this reason the objective of the technological proposal is to develop a web and mobile application for e-commerce, for the development of the project different types of research were applied such as mixed research, bibliographic research and field research. In addition, techniques and instruments of data collection interview, survey and observation with the purpose of obtaining information of the problematic situation from primary sources. At the same time, agile practices were used for the implementation of the web and mobile application, including user stories, product backlog, prioritization and estimation, sprint planning, among others. Finally, software tools such as Python, PostgreSQL, Django, Lucidchart, HTML, CSS, Java Script, Android and Visual Studio Code were used. As a result, the inadequate sales management process of the company SopTec pc was solved, since the system allows to provide information about the company, contacts, online shopping, customer information registration, product management, stock management and shipping method. The project is concluded by deploying the application on the web server.